2013
DOI: 10.1016/j.bbadis.2013.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione peroxidase contributes with heme oxygenase-1 to redox balance in mouse brain during the course of cerebral malaria

Abstract: Oxidative stress has been attributed both a key pathogenic and rescuing role in cerebral malaria (CM). In a Plasmodium berghei ANKA murine model of CM, host redox signaling and functioning were examined during the course of neurological damage. Host antioxidant defenses were early altered at the transcriptional level indicated by the gradually diminished expression of superoxide dismutase-1 (sod-1), sod-2, sod-3 and catalase genes. During severe disease, this led to the dysfunctional activity of superoxide dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…In the present study, miR-155 -/-infected mice also had significantly lower Ho-1 mRNA levels than w/t mice at d 6 post-infection. This finding is consistent with a previous study of ECM, where Ho-1 mRNA expression was found to be progressively and significantly elevated through the course of infection in multiple regions of the brain in ECM-susceptible mice (46). Even if HO-1 is associated with protection in the ECM model, this association may be lost in the absence of miR-155.…”
Section: Mir-155supporting
confidence: 82%
“…In the present study, miR-155 -/-infected mice also had significantly lower Ho-1 mRNA levels than w/t mice at d 6 post-infection. This finding is consistent with a previous study of ECM, where Ho-1 mRNA expression was found to be progressively and significantly elevated through the course of infection in multiple regions of the brain in ECM-susceptible mice (46). Even if HO-1 is associated with protection in the ECM model, this association may be lost in the absence of miR-155.…”
Section: Mir-155supporting
confidence: 82%
“…The role of ROS/RNS in the pathogenesis of ECM is indeed unclear [8, 9, 11, 12, 40, 41]. Antioxidant treatments can be protective against ECM [41] and lipid peroxidation increased and cerebral thiols decreased in late-stage ECM [40, 42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many antioxidant treatments can also have effects on immune function [12, 46], which may partly explain their efficacy in ECM. Furthermore, although expression of some genes involved with oxidative stress is reduced in ECM [11], these seem to be compensated by increased anti-oxidant gene promotion [11, 47]: molecular markers of ROS damage (ROS-modified proteins) are largely unchanged [11, 12], mitochondrial function is preserved in ECM [8] and genetic removal of the primary endogenous reactive species generator NADPH oxidase does not improve ECM outcome [12]. Furthermore, poly(ADP-ribose) polymerase-1 knock-out mice are not protected from ECM, indicating that cytopathic hypoxia is not driving ECM [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antioxidative treatment protects mice from CM (Thumwood et al 1989), even though no increased levels of protein carbonylation nor oxidation are found in the brain, and mice deficient in NADPH oxidase are as susceptible as WT to develop CM (Sanni et al 1999). The antioxidative defense in the brain of mice with CM appears to be mediated by HO-1 and glutathione peroxidase, whereas the expression of SOD and catalase is decreased (Linares et al 2013). Antioxidative adjunctive therapeutic treatment of severely ill P. falciparum patients was not effective (Charunwatthana et al 2009).…”
Section: Cytokines and Other Soluble Inflammatory Mediatorsmentioning
confidence: 99%